Legal Protection of Citizens' Education Regarding Freedom of the Press as an Implementation of the Indonesian Legal State - Fitria Wilandari, Devi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The press, as an information medium, is a tool for conveying or obtaining various important information, such as political, entertainment, social, and other issues. Through the press, people can learn or obtain useful information. Meanwhile, the press, as an educational medium, means that the information or news disseminated through the media also serves to educate, contain truth, educate, and encourage good deeds. Freedom of the press constitutes one of the fundamental pillars of democracy and the rule of law. In Indonesia, press freedom is constitutionally guaranteed under Articles 28E and 28F of the 1945 Constitution and further regulated by Law Number 40 of 1999 concerning the Press. This article aims to analyze the legal protection of press freedom in Indonesia and the challenges faced in its implementation. This study employs normative legal research using statutory and conceptual approaches. The findings indicate that although press freedom is normatively well protected, practical challenges remain, including the criminalization of journalists, the use of ambiguous provisions under the Electronic Information and Transactions Law (EIT Law), and political as well as economic pressures on media institutions. Therefore, strengthening regulatory frameworks, ensuring consistent law enforcement, and enhancing media independence are essential to guarantee responsible press freedom within the framework of a rule-of-law state.